Study on Sinkhole Formation: A Comparative Analysis of Natural Vs Human-Induced Factors - GHAAYESHTHREE SUBRAMANIAM,; MOHD ARIF BIN ROSLI, (Progress in Engineering Application and Technology, 2025)
This study presents a comparative analysis of sinkhole formation caused by natural and human-induced factors. It focuses on environmental impacts and examines the contribution of geological factors such as karst features, groundwater dissolution, and erosion, alongside anthropogenic triggers like urban development, groundwater extraction, and mining. A structured expert questionnaire was used to collect responses from professionals in geotechnical, environmental, and planning fields. Analysis using SPSS with Frequency Index and Mean Ranking revealed that while natural causes are foundational, human-induced activities significantly amplify the frequency and severity of sinkhole events, particularly in urban areas. The study recommends mandatory geotechnical investigations, better drainage design, and policy enforcement as key mitigation strategies. This paper highlights the need for sustainable land-use planning to reduce sinkhole risks effectively.